ANALISA PERBANDINGAN BEBERAPA METODE PENENTUAN POWER ENGINE KAPAL POLBENG II - Muhammad Helmi; Budhi Santoso; Edy Haryanto, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Starting from the learning development process to produce products carried out in the Department of Shipbuilding Engineering, so that one of the products produced in student learning is a ship drawing design product in the form of a Lines Plane drawing. Starting from this lines plane image, the author conducted a power engine study using the Maxsurf Resistance program, so that a feasible resistance method could be determined. The feasible methods used are Compton, Slenderbody and KR Barge Resistance, from these three methods produce engine power at a ship speed of 15 knots. The compton method reads at a speed of 10.5 knots with an engine power of 22.8 Hp, the slenderbody method at a speed of 15 knots the required engine power is 54.3 Hp and for the KR Barge Resistance method at a speed of 15 Knots requires an engine power of 122.4 Hp. Based on the method used, it can be determined that the feasible method is the slenderbody method.